Modeling of interlayer excitons in van der Waals heterostructures - Ovesen, Simon (My University, 2017)
The field of TMD (Transition Metal Dichalcogenide) monolayers is an active one due to certain interesting properties such as a direct band gap, strong spin-orbit coupling and a remarkably large Coulomb interaction leading to strongly bound excitons. For technical applications heterostructures composed of stacked monolayers are also a huge topic of interest. Recent experimental studies of the photoluminescence of these structures show evidence of the existence of interlayer excitons. The aim of this thesis is to propose a mechanism for the formation and dynamics of these interlayer excitons in a bilayer heterostructure. For this purpose the second quantization formalism and tight binding approach are employed. Aside from the free, optical, carrier-photon, carrier-phonon and Coulomb interactions that have already been studied for monolayers, a tunneling interaction that couples the two layers is also included. For the intralayer Coulomb potential the familiar Keldysh potential is used, while an extension of it derived here is used as the interlayer potential. The Hamiltonian constructed from these contributions is then converted to the excitonic picture as opposed to the often used electron-hole picture. By using this excitonic Hamiltonian in the Heisenberg equation of motion, equations for the microscopic polarization and exciton densities are derived analytically and solved numerically. From these equations the physically measurable quantities absorption and photoluminescence are computed. Parameters used in the tunneling interaction are then varied to attempt to fit the results to the experimentally measured photoluminescence of an MoSe2 - WSe2 heterostructure.
Keywords: Fysik; Physical Sciences